1984
DOI: 10.1346/ccmn.1984.0320503
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxidation State of Octahedral Iron on Clay Swelling

Abstract: Abstract-Three montmorillonites and a nontronite were reduced by sodium dithionite to obtain different amounts of Fe 2+ in their octahedral sites. The mass ratio of water to clay, mJmo, was determined as a function of Fe z+ at several values of the swelling pressure, II. The value mJmo decreased markedly with increasing Fe 2 § at each value of II for each clay. Moreover, curves of II vs. mJmc for the different clays were displaced downwards as Fe 2+ increased. A straight line was obtained when ln(II + 1) was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
75
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 14 publications
(10 reference statements)
9
75
0
Order By: Relevance
“…Reduced gels were prepared by suspending 100 mg of stock clay in 30 ml of citrate-bicarbonate buffer solution (Stucki et al, 1984a), adding 100 nag of sodium dithionite (Na2S204) salt, and heating at 70~ under an inert atmosphere in an open-system reaction vessel for 2 hr (Komadel et aL, 1990), bringing the clay to about 50% reduction. The clay thus reduced was then washed by centrifugation to a solute concentration of about 10 -4 N, and the suspension was placed in a pressure cell described by Stucki et al (1984b) under 10 kPa N 2 gas pressure. Excess liquid was expelled from the sample through a porous membrane filter (0.025-ttm pore diameter) at the bottom of the pressure cell, forming a clay gel on the membrane surface.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced gels were prepared by suspending 100 mg of stock clay in 30 ml of citrate-bicarbonate buffer solution (Stucki et al, 1984a), adding 100 nag of sodium dithionite (Na2S204) salt, and heating at 70~ under an inert atmosphere in an open-system reaction vessel for 2 hr (Komadel et aL, 1990), bringing the clay to about 50% reduction. The clay thus reduced was then washed by centrifugation to a solute concentration of about 10 -4 N, and the suspension was placed in a pressure cell described by Stucki et al (1984b) under 10 kPa N 2 gas pressure. Excess liquid was expelled from the sample through a porous membrane filter (0.025-ttm pore diameter) at the bottom of the pressure cell, forming a clay gel on the membrane surface.…”
Section: Methodsmentioning
confidence: 99%
“…Stucki et al (1984b) and Lear and Stucki (1989) showed that the interlayer repulsive force in smectite, i.e., swelling in water, decreases with increasing Fe(II) content, and that the specific surface area, as measured by ethylene glycol-monoethylether adsorption, is greatly diminished. Chen et al (1987), Lear and Stucki (1989), and Khaled and Stucki (1991) also observed a marked increase in the fixation of interlayer cations (Na +, K § Ca 2+, Cu 2+, and Zn 2+) by the chemical reduction of structural Fe.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies (Foster, 1953;Egashira and Ohtsubo, 1983;Stucki et al, 1984b) have reported that the swelling of aqueous dispersions ofaluminosilicate clay minerals is substantially altered by the oxidation state of octahedral Fe in the clay crystal structure. The underlying basis for this phenomenon, however, is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The swelling of clays in their natural oxidation state is commonly believed to be the result of electrical double-layer repulsion (van Olphen, 1963), but surface hydration is considered by many to be a more favorable concept (Low, 1987). According to the double-layer repulsion theory, the swelling pressure, H, increases with increasing surface charge density, a (van Olphen, 1963;Viani et al, 1983), and, by definition, a is the electrostatic charge per unit area of the clay surface, which is commonly obtained from the relation a = 60/Sm, (la) where ~ is the cation-exchange capacity and Sm is the specific surface area, i.e., that portion of the total surface area that is available to water and exchangeable ions.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding these systems is of significant importance because they serve as an important source for electrons in redox reactions in various geochemical environments. [32][33][34][35] Moreover, the change of the Fe oxidation state has a profound impact on the electronic structure of the surfaces of these minerals, such as in their adsorption properties and chemical activity.…”
mentioning
confidence: 99%